Report of the Prohibition Enquiry Committee - Planning Commission (Planning Commission, 1955)
The Prohibition Enquiry Committee was appointed by the Plan- Appointment of Planning Commission, Government of India, in Committee and pursuance of Resolution No. PC/Proh/1/54, terms of reference dated the 16th December 1954, which specified the purpose as follows: “Article 47 of the Constitution lays down as a Directive Principle of State Policy that the State shall endeavour to bring about prohibition of the consumption, except for medicinal purposes, of intoxicating drinks and of drugs which are injurious to health. Experience gained in a number of States in implementing the programme of prohibition has suggested the need for further study of problems connected with administration, co-operation and support from the community, financial aspects, co-operation between neighbouring areas, etc. With the object of developing a national programme for the fulfilment, with wide public support, of the Directive Principle of the Constitution, it is desirable at this stage to review the experience gained and to find solutions for the problems and difficulties encountered in recent years.
Planning Commission Government of India